2010
DOI: 10.1111/j.1365-2966.2010.16375.x
|View full text |Cite
|
Sign up to set email alerts
|

Star formation and AGN activity in SDSS cluster galaxies

Abstract: We investigate the recent and current star formation activity of galaxies as function of distance from the cluster center in a sample of 521 SDSS clusters at z<0.1. We show that when the BCGs are excluded from the galaxy sample, there is no evidence for mass segregation in the clusters, so that differences in cluster and field populations cannot simply be attributed to different mass functions. We find a marked star formation-radius relation in that almost all galaxies in the cluster core are quiescent, i.e. h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
183
4
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 196 publications
(209 citation statements)
references
References 97 publications
(140 reference statements)
21
183
4
1
Order By: Relevance
“…Our analysis, which adopts the criteria of Cid Fernandes et al (2010Fernandes et al ( , 2011 for the classification of nuclei, is in full agreement with both Kauffmann et al (2004) and Von der Linden et al (2010). We conclude that, even after eliminating the effects of morphology segregation (by counting the frequency of nuclear activity in the proper bins of Hubble type), there is a residual decline in the frequency of nuclear activity (either triggered by black holes or sustained by the star formation) with increasing galaxy density (see Fig.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Our analysis, which adopts the criteria of Cid Fernandes et al (2010Fernandes et al ( , 2011 for the classification of nuclei, is in full agreement with both Kauffmann et al (2004) and Von der Linden et al (2010). We conclude that, even after eliminating the effects of morphology segregation (by counting the frequency of nuclear activity in the proper bins of Hubble type), there is a residual decline in the frequency of nuclear activity (either triggered by black holes or sustained by the star formation) with increasing galaxy density (see Fig.…”
Section: Discussionsupporting
confidence: 77%
“…The decrease in their frequency with increasing galaxy density is mostly due to the decrease in the frequency of galaxies that are able to host AGNs (morphology segregation), but − to a lesser extent -is due to a genuine extra decrease in AGN frequency in high density environments. Von der Linden et al (2010) argued that galaxies in dense environments are less likely to host a powerful optical AGN or a star-forming nuclear region. The frequency of optical AGNs in early-type galaxies declines in high density environments (by approximately a factor of two between the field and the center of clusters).…”
Section: Discussionmentioning
confidence: 99%
“…Some observational studies (e.g. Balogh et al 2000;Haines et al 2009;von der Linden et al 2010;Rasmussen et al 2012;Geha et al 2012) find an enhanced quiescent fraction of centrals in the vicinity of massive neighbour haloes out to four times the virial radius. Other studies find, however, no such trend.…”
Section: Introductionmentioning
confidence: 99%
“…A spectroscopic study of 521 clusters in the SDSS by von der Linden et al (2010) indicated that the star formation rates of galaxies decline slowly during the infall into a cluster, with the most rapid quenching only occurring at the centres of clusters. The inferred quenching timescales were therefore long, roughly a few Gyrs, which is comparable to the cluster crossing time.…”
Section: Introductionmentioning
confidence: 99%